The Influence Of Internal Audit, HR Competency, and Information Technology-Based Internal Control On The Quality Of Financial Reports Of PTPN IV Regional II Medan with Management Commitment as a Moderating Variable - Riza Milianda Kasa; Rahima Br Purba (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the effect of internal audit, human resource competence (HR), and information technology-based internal control on the quality of financial reporting at PTPN IV Regional II Medan, with management commitment as a moderating variable. The method used in this study is Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. Data was collected from 50 employees in the accounting and finance department through a questionnaire to measure their perceptions of the variables studied. The results of the study indicate that internal audit and HR competence have a significant impact on the quality of financial reporting, while management commitment and information technology-based internal control do not show a significant direct effect. Furthermore, the moderation test results show that management commitment does not strengthen or weaken the relationship between the independent variables and the quality of financial reporting. This study contributes theoretically to the understanding of the relationship between factors influencing the quality of financial reporting and provides practical recommendations for PTPN IV Regional II to improve the quality of financial reporting through strengthening internal audit and HR competence.